The functional response of human monocyte-derived macrophages to serum amyloid A and Mycobacterium tuberculosis infection - Malwina Kawka; Renata Płocińska; Przemysław Płociński; Jakub Pawełczyk; Marcin Słomka; Justyna Gatkowska; Katarzyna Dzitko; Bożena Dziadek; Jarosław Dziadek (Frontiers in Immunology, 2023)
IntroductionIn the course of tuberculosis (TB), the level of major acute phase protein, namely serum amyloid A (hSAA-1), increases up to a hundredfold in the pleural fluids of infected individuals. Tubercle bacilli infecting the human host can be opsonized by hSAA-1, which affects bacterial entry into human macrophages and their intracellular multiplication.MethodsWe applied global RNA sequencing to evaluate the functional response of human monocyte-derived macrophages (MDMs), isolated from healthy blood donors, under elevated hSAA-1 conditions and during infection with nonopsonized and hSAA-1-opsonized Mycobacterium tuberculosis (Mtb). In the same infection model, we also examined the functional response of mycobacteria to the intracellular environment of macrophages in the presence and absence of hSAA-1. The RNASeq analysis was validated using qPCR. The functional response of MDMs to hSAA-1 and/or tubercle bacilli was also evaluated for selected cytokines at the protein level by applying the Milliplex system.FindingsTranscriptomes of MDMs cultured in the presence of hSAA-1 or infected with Mtb showed a high degree of similarity for both upregulated and downregulated genes involved mainly in processes related to cell division and immune response, respectively. Among the most induced genes, across both hSAA-1 and Mtb infection conditions, CXCL8, CCL15, CCL5, IL-1β, and receptors for IL-7 and IL-2 were identified. We also observed the same pattern of upregulated pro-inflammatory cytokines (TNFα, IL-6, IL-12, IL-18, IL-23, and IL-1) and downregulated anti-inflammatory cytokines (IL-10, TGFβ, and antimicrobial peptide cathelicidin) in the hSAA-1 treated-MDMs or the phagocytes infected with tubercle bacilli. At this early stage of infection, Mtb genes affected by the inside microenvironment of MDMs are strictly involved in iron scavenging, adaptation to hypoxia, low pH, and increasing levels of CO2. The genes for the synthesis and transport of virulence lipids, but not cholesterol/fatty acid degradation, were also upregulated.ConclusionElevated serum hSAA-1 levels in tuberculosis enhance the response of host phagocytes to infection, including macrophages that have not yet been in contact with mycobacteria. SAA induces antigen processing and presentation processes by professional phagocytes reversing the inhibition caused by Mtb infection.